Disclosure among youth stopped by the police: Repercussions for mental health - Kristin Turney; Amanda Geller; Sarah K. Cowan (Elsevier, 2022)
Police contact is a common and consequential experience disproportionately endured by youth of color living in heavily surveilled neighborhoods. Disclosing police contact to others (including parents, siblings, or friends) may buffer against the harmful mental health repercussions of police contact, but little is known about the relationship between disclosure of police contact and mental health. We use data from the Fragile Families and Child Wellbeing Study, a cohort of urban children born around the turn of the 21st century and followed through age 15, to examine the relationship between disclosure of police contact and mental health among youth. Results suggest three conclusions. First, youth who experience police contact (regardless of whether they disclose this contact) report more depressive symptoms and anxiety than youth who do not experience police contact. Second, among youth who experience police contact, disclosure is associated with significantly less anxiety (but is not significantly associated with depressive symptoms). Third, this protective nature of disclosure is concentrated among Black youth and boys. Taken together, these findings suggest that disclosing police contact, particularly for groups most likely to experience it, may ameliorate some of the harmful mental health repercussions of this contact for youth.